DIMENSI I’JAZ AL-QUR’AN PADA SUMBER DAYA LAUT: ANALISIS SURAH AL-NAHAL AYAT 14 - Santi Marito Hasibuan; Agustina Damanik; Miranda Nasati Pohan (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
This study aims to axamine the natural resources contained in Surah al-Nahl verse 14. This study is library research, by making the Qur’an and the book of interpretation as primary seurces or main seurces. In addition, the author also refers to hadith books and books related to the theme as additional references (secondary). Based on the results of the library research conducted by the researcher, it can be seen that in surah al-Nahl verse 14 there is i’jaz al-Qur’an. There are at least 3 natural resources in the sea that have i’jaz (excellence), namely: fish, jewelry and sailing ships. When mentioning fish, the qur’an uses the term lahman thariyya (fresh meat), fish is characterized with the word fresh as a signal for humans to eat fish when it is still fresh, because fresh fish contains high protein. This is in line with the findings of health science which explains that fish that have lost their freshness are included in dangerous foods. Jewelry in this verse is called hilyah (pearls and marjan). The word mawakhir in this verse is interpreted as a voyage. This means that mawakhir is described as a means of sea transportation or ports axisted, the qur’an already described them. Furthermore, maritime transportation receives a significant amount of discussion in the qur’an, while land transportation, especially in the desert, ia not a topic of interest.